Regional aging and longevity characteristics in China. (November 2016) - Wang, Li; Li, Yonghua; Li, Hairong; Holdaway, Jennifer; Hao, Zhe; Wang, Wuyi; Krafft, Thomas
Abstract: The factors that influence the length of human life are complex and longevity remains a controversial topic, particularly in China. This paper demonstrates the spatial patterns and changes of the elderly group (65 years old and over), the oldest old (80 years old and over) and the centenarians in China in the last decade, analyzes the influence of economic development on aging, and in the end, using a case study, explores the characteristics of the centenarians' behavior. The results indicate that high elderly and the oldest old proportions are more common in regions with higher socio-economic development and that have a favorable climate. Centenarian distribution pattern is less influenced by economic but only for few regions. Lifestyle factors, such as sufficient sleep, positive mental state and a light diet are also largely found among the centenarian group.